2019
DOI: 10.1002/art.41083
|View full text |Cite
|
Sign up to set email alerts
|

Population‐Specific Patterns of Epigenetic Defects in the B Cell Lineage in Patients With Systemic Lupus Erythematosus

Abstract: Objective. To determine the stage of B cell development at which a systemic lupus erythematosus (SLE)associated DNA methylation signature originates in African American (AA) and European American (EA) subjects, and to assess whether epigenetic defects in B cell development patterns could be predictive of SLE status in individual and mixed immune cell populations.Methods. B cells from AA patients (n = 31) and EA patients (n = 49) with or without SLE were sorted using fluorescence-activated cell sorting into 5 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…18 Interestingly, 1 study has shown that the pattern of hypomethylation in IFN-regulated genes occurs early in B-cell development in African Americans, and could distinguish African American SLE patients from healthy controls in several B-cell subsets, whereas DNA methylation changes in European American SLE patients occurred in mature Bcell stages. 59 Altogether, evidence from epigenetic studies suggests the existence of DNA methylation differences between populations that might point to etiological differences between African American SLE patients compared to those from other populations.…”
Section: Discussionmentioning
confidence: 99%
“…18 Interestingly, 1 study has shown that the pattern of hypomethylation in IFN-regulated genes occurs early in B-cell development in African Americans, and could distinguish African American SLE patients from healthy controls in several B-cell subsets, whereas DNA methylation changes in European American SLE patients occurred in mature Bcell stages. 59 Altogether, evidence from epigenetic studies suggests the existence of DNA methylation differences between populations that might point to etiological differences between African American SLE patients compared to those from other populations.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest of these genome-wide studies interrogated 27,578 CpG sites in 12 SLE patients and 12 healthy controls using the Illumina Infinium HumanMethylation27 Beadchip, and identified 336 differentially methylated genes, the majority of which were hypomethylated in the cases relative to the controls [ 11 ]. Subsequent studies have examined genome-wide methylation in larger samples of SLE patients using the HumanMethylation450 Beadchip (>485,000 CpG sites) in a number of cell types, including naïve CD4+ T cells [ 12 , 13 , 14 , 15 , 16 ], memory and regulatory T cells [ 17 ], CD19+ B cells [ 17 ], CD14+ monocytes [ 14 , 17 ], granulocytes [ 14 ], neutrophils [ 18 ], and whole blood or peripheral blood mononuclear cells (PBMC) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Differential methylation has not only been observed when comparing SLE patients to healthy controls, but similar patterns have been identified in SLE patients with nephritis [ 12 , 19 , 22 ], skin involvement [ 13 ], specific antibodies [ 20 ], and pediatric SLE [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypomethylation is observed in the vicinity of type 1 IFN-regulated genes in lupus, consistent with the characteristic IFN signature ( 96 99 ). A recent study ( 100 ) found that ethnicity influences these DNA methylation patterns. They were most pronounced in African American SLE patients compared to healthy women and were apparent as early as the transitional B cell stage in African American patients.…”
Section: Altered Chromatin Accessibility In Sle B Cellsmentioning
confidence: 99%